2016
DOI: 10.14238/sp10.6.2009.367-72
|View full text |Cite
|
Sign up to set email alerts
|

Komplikasi Jangka Pendek dan Jangka Panjang Diabetes Mellitus Tipe 1

Abstract: Latar belakang. Diabetes mellitus tipe 1 (DM tipe-1) adalah kelainan metabolik yang disebabkan oleh reaksi autoimun yang menyebabkan kerusakan sel β pankreas dan terjadi pada hampir semua anak yang menderita diabetes. Dalam perjalanan DM tipe-1, sering timbul komplikasi jangka pendek dan jangka panjang. Tujuan. Mengetahui frekuensi komplikasi jangka pendek yaitu ketoasidosis dan jangka panjang yaitu nefropati dan retinopati berdasarkan kontrol metabolik, lama menderita diabetes, dan biaya pengobatan. Metode. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
0
10
0
3
Order By: Relevance
“…21 Himawan et al also reported a DKA prevalence to be 43.6% in female patients (17 patient) and 33.3% in male patients (13 patient), presented in early diagnosis of DKA, the prevalence was 86.7% in 26 patients and many of them were female. 5 Alphonsus and Emeka reported from 37 patients, the males:females ratio was 1:1.5. 18 Factors that precipitate DKA in children and adolescents include emotional stress, infection, missed insulin injection, trauma, pancreatitis, and poor compliance to medication in patients with known diabetes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…21 Himawan et al also reported a DKA prevalence to be 43.6% in female patients (17 patient) and 33.3% in male patients (13 patient), presented in early diagnosis of DKA, the prevalence was 86.7% in 26 patients and many of them were female. 5 Alphonsus and Emeka reported from 37 patients, the males:females ratio was 1:1.5. 18 Factors that precipitate DKA in children and adolescents include emotional stress, infection, missed insulin injection, trauma, pancreatitis, and poor compliance to medication in patients with known diabetes.…”
Section: Discussionmentioning
confidence: 91%
“…4 Himawan et al reported a DKA prevalence of 43.6% in girls. 5 The long-term effects of diabetes mellitus include retinopathy, chronic kidney disease (nephropathy), neuropathy, and dyslipidemia. 2 In Indonesia, DKA is often unidentified and therapy inadequate, due to several factors such as a dearth of health care facilities in remote areas, a culture of avoiding doctors, financial constraints, and regulations governing access to care.…”
mentioning
confidence: 99%
“…Berdasarkan data ISPAD pada tahun yang sama menyebutkan bahwa perbedaan jenis kelamin terhadap Locus HLA-DR dan HLA-DQ di regio kelas II dianggap insiden DM tipe 1 tidak terjadi secara keseluruhan di mempunyai risiko terhadap terjadinya DM tipe 1 (25). seluruh dunia (5). Adanya perbedaan ini disebabkan oleh Selain itu, pengaruh genetik tertentu dan pengaruh perbedaan populasi, ras, dan jumlah subjek penelitian lingkungan yang berbeda dapat mempengaruhi kadar (13,14).…”
Section: Endokrinologi Anak Pengurus Pusat Ikatan Dokterunclassified
“…Insulin dose adjustment aims to achieve optimal metabolic control, without increasing the risk of hypoglycemia and without neglecting the quality of life of patients both short and long term. During the 'honeymoon' period the total daily dose of insulin is < 0.5 IU/kgBW/day, the child before puberty (outside the 'honeymoon' period) in the dose range of 0.7-1.0 IU/kgBW/day, while during puberty the need increases above 1 IU to 2 IU/kgBW/day [23,24]. This may be the case in this study, with mean age of 12.46 ± 2.99 years for the K1 group and 12.15 ± 3.26 years for the K2 group which is the age of puberty, so that an average insulin dose of 11.14 ± 0.16 and 1.19 ± 0.29 IU/kgBW/ day for each group in order.…”
Section: Subject Characteristicsmentioning
confidence: 99%